ANTI-SUICIDE CAMPAIGN STUDY GORONTALO & SOUTH SUMATERA PROVINCIAL HEALTH DEPARTMENT POSTERS 2019 - Rifandary, Dina; Kasmana, Kankan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Suicide is the most common cause of death, becoming a humanitarian emergency case, which threatens the survival of the nation’s next generation. In the anti-suicide campaign, posters are used as information media. The purpose of the study was to examine the symbolic meaning and visual elements in the design of campaign posters, 2 Health Offices (Gorontalo Province and South Sumatra). The method used was qualitative with Van Zoest’s semiotic approach (syntactic, semantic, and pragmatic analysis). The results showed that the posters had visual representations of emotions: darkness, loneliness, or hopelessness; the poster narratives contained motivating quotes and information on aid resources. In conclusion, the visual elements on the poster form a visual message in raising awareness to combat suicide. The impact of the research is that it can educate, reduce the stigma of suicide, and help policy makers and designers design campaign posters with appropriate messages and effective strategies